Computed Tomographic findings of maxillofacial SCC and Undifferentiated carcinoma - Adineh Javadian Langaroodi; Ali Bagherpour; Mahdi Aghili; Mahdieh Taleb Mehr; Mahrokh Imanimoghaddam; Omid Mahjoob (Cumhuriyet University, 2015)
Abstract:Objectives: Tomographic findings contribute enormously to the accurate diagnosis of malignant lesions in due time and/or at imminent stages. This study investigates CT-scan findings of maxillofacial SCC and undifferentiated carcinoma.Study design:  CT images of 61 maxillofacial malignant tumors included 42 SCCs and 19 undifferentiated carcinomas were evaluated based on the location, internal density, border, bone destruction and expansion, periosteal reaction, emphysema, calcification, loss of facial and fat plane, and fat plane reticulation, by two expert radiologists separately. The data were analyzed, using Chi-square and Fisher's exact test.Results: Isodense/homogeneous (78.7%) and total heterogeneous enhancement (87.8%) appearance were the most common internal patterns detected before and after injection of contrast, respectively. There was a significant association between borders and pathology of our two lesions (p= 0.007).Conclusions: It is highly unlikely to diagnose the tumor histopathology based merely on its tomography patterns; however it is feasible to determine its aggressive nature.      Key words: Computed tomography, SCC, undifferentiated carcinoma, maxillofacial region